Multi-Proxy Environmental Reconstruction of the Covacha de los Zarpazos in Galería Site (Atapuerca, Spain) - D'Arcangelo, Serena; Martín Hernández, Fátima; María Parés, Josep; Álvaro Gallo, Ana; Ortega, Ana Isabel; García-Medrano, Paula; Cáceres, Isabel (Earth and Planetary Science, 2024)
Magnetic properties of iron oxides provide invaluable data for environmental reconstruction during sediment deposition. Encouraged by the results of our previous studies in the near Gran Dolina site, we investigate the GI waterlain facies sediments that fill Galería Complex cave (Sierra de Atapuerca, Spain), in particular the Covacha de los Zarpazos cave considering two vertical profiles at different walls and comparing them with two profiles previously analysed. For the first time in this cave, we propose a correlation among these two walls based on the low field susceptibility values. An environmental reconstruction is proposed based on the pedogenesis and weathering processes, and water activity influencing the composition, concentration and grain size of magnetic minerals. In order to have a more comprehensive interpretation, elemental geochemistry was also analysed. The results allow to identify three different sections with the alternation of environmental characteristics. ER